O fishbowl no ensino de anatomia: contribuições para uma aprendizagem colaborativa - Morano, Domingos Antonio Clemente Maria Silvio (2023)
Fishbowl is an active teaching methodology whose group discussion format promotes dialogue and sharing of experiences among students during the session and allows everyone to have equal opportunities to express their opinions and points of view during the mediated classes, expressing themselves through and their scientific knowledge. Thus, the use of this methodology is justified to teach concepts of endocrine system anatomy to undergraduate students duly enrolled in the medical, dental, and pharmacy courses at UFC who agreed to participate in the activity. However, there is little evidence of the use of this methodology to guide faculty on how best to implement Fishbowl. Based on the scarcity of use of this method in teaching human anatomy, we sought to promote its efficacy when applied to this public. The objective of this work was to investigate the use of the Fishbowl in the teaching and learning process of human anatomy. A quasi-experimental study with a quantitative approach was carried out with students of the anatomy discipline on the subject endocrine system. The technique used was the open Fishbowl. The Graphpad Prism version 7.0 program was used for data analysis, and data with a p-value <0.05 were considered significant. It was observed that there was no statistically significant difference between the ages of the participants (p>0.05). In our studies, Fishbowl was found to be more effective for teaching anatomy compared to conventional teaching (p<0.05). Fishbowl proved to be a satisfactory teaching technique for students when compared to the usual lecture. It was found that the Fishbowl allowed the educational process to be carried out with greater interaction in a more playful and meaningful way. Moreover, the students took the lead in the teaching and learning processes, participating more effectively in the classes. Thus, the Fishbowl presented itself as an active didactic-pedagogical proposal in the teaching and learning processes of human anatomy.